CONTINOUS PROFESSIONAL DEVELOPMENT OF EFL TEACHERS - Muhammadiyeva, Halima (Журнал иностранных языков и лингвистики, 2021)
The article discusses the strategic role of continuous professional development of EFL teachers in the education system and the need for professional development of teachers of foreign languages.